Building walls and dissolving borders the challenges of alterity, community and securitizing space - Stephenson, Max O. (Max Olin) Jr. 1955-; Zanotti, Laura (Ashgate Publishing Routledge, 2013)
This book explores walls as the consequence of a changing web of social relationships. Whether walls are physical objects on the landscape or metaphors for difference among specific groups or communities, the writers consider them as heterotopias, powerful sites around which ways of living together are contested and transformed. They also investigate how architectural planning concerning walls may de facto become a means of waging war, as well as how demolishing walls may give way to new ways of imagining security